Sistem Pakar Diagnosis Penyakit Pada Kambing Menggunakan Metode Dempster Shafer - Agus Ardiansyah; Lailil Muflikhah; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Disease in goat cattle is an important thing to be considered, because it can cause losses for breeders can even cause the death of goat. Examination disease periodically are necessary to keep goats from disease. The investigation disease goats cannot be done by any person as between types of disease with this shows a tendency to having uncertainty. This makes it difficult for farmers to do early treatment and do not know what to do without an expert/veterinarian. Based on these problems, the authors create an expert system capable of diagnosing disease in goats as is usually done by an expert/veterinarian. This expert system uses the Dempster Shafer method. The Dempster Shafer method is a mathematical theory of evidence. The theory can provide a way of combining evidence from multiple sources and bringing in or providing a level of trust (represented by a trust function) which takes from all available evidence. Based on the results of the tests conducted on 32 test cases, obtained the average result of precision of 93%, 96% recall, and accuracy for f-measure of 94%